PERAN LINGKUNGAN SOSIAL TERHADAP KETAKUTAN MENIKAH PADA MAHASISWA GENERASI Z PRODI BIMBINGAN DAN KONSELING KELAS 01 ANGKATAN 2022 UNIVERSITAS SLAMET RIYADI - Putri, Tasya Amanda; Jawandi, Ahmad; Adi Putro, Eko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The purpose of this study is to determine how the social environment influences the fear of marriage among Generation Z students in the Guidance and Counseling study program, Class 01 of the 2022/2023 cohort. This research was conducted at Slamet Riyadi University, Surakarta. The subjects of this study were Generation Z students from the Guidance and Counseling program, Class 01 of the 2022 cohort, who experience fear of marriage. The research instruments used were observation guidelines, interview guidelines, and documentation. Data collection techniques were carried out through observation, interviews, and documentation. The data obtained were then analyzed through several stages, including summarizing, drawing conclusions, and verification. Based on the results of data analysis, it was found that the social environment does influence the fear of marriage, especially among Generation Z students. A poor social environment can influence and create negative perceptions of marriage among Generation Z students, which is triggered by cases of patriarchy, domestic violence (KDRT), and other issues that circulate and occur in their surrounding environment.